Challenges and management of the nursing staff at the central sterilized material center (Research, Society and Development, 2021)
Objective: To identify the main challenges described and the management of the nursing team at the Central Sterile Material Center. Methodology: This is an integrative review of qualitative nature that used 12 articles in Portuguese and English extracted from the Scientific Electronic Library Online (Scielo) and Public Medline (PubMed), with the help of descriptors available in the Health Science Descriptors (DeCS) in Portuguese and English. Results: The nursing staff in front of the CME is routinely exposed to risks by chemical, physical and biological agents, as well as risk related to ergonomic factors. These health risk problems can be added to the work overload, and the lack of experience and training for the development of their activities. Conclusion: Given the discussion of this article, the nursing practice at the Central Sterilized Material Center is surrounded by challenges and problems that need more attention from the institutional management team, as well as from its technical leaders in the segments of personnel management and continuing education.